The Effect of Role-Playing Method on Student's Confidence in Indonesian Language Subjects - Ayu Tusaroh; Juhji Juhji (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study was to determine the effect of the method of playing a role in student confidence in Indonesian subjects. The quasi-experimental method is used as a research method with the Non-Equivalent Control Group Design research design. The population of all students in the primary school state of Cilaku. Samples were taken as many as 48 students from the VA class of 24 students as the control class and the VB class of 24 as the experimental class. The data analysis technique used in determining the average, calculating the standard deviation, normality test, homogeneity test, and t-test. The results showed that the variable of students 'confidence using the role-playing method obtained an average posttest score of 78.33. In contrast, the results of students' confidence using conventional learning received an average posttest score of 66.17. Then the hypothesis test is performed, which shows the results of t count 4.09 and t table = 2.074 with n-2 = 24-2 = 22 and a significance level of 0.05. Based on the t count ˃ t-test criteria, Ha is accepted, and Ho is rejected. Thus it can be concluded that the role-playing method influences students' confidence in Indonesian subjects.